PENGARUH KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN TOKO BUKU FADIRA PEKANBARU - Fakhri, Rizqi (Sekolah Tinggi Ilmu Ekonomi Riau, 2022)
Testing the Customer Satisfaction variable on customer loyalty through the t-test can be seen that tcount is greater than ttable (5,770>2,042). Thus it can be concluded that the variable Customer Satisfaction (X) has a positive and significant effect on Customer Loyalty at Fadira Bookstore Pekanbaru. The results of simple linear regression show Y=a+bX, namely: Y= 9,251 + 0,814X. From these equations it can be concluded that the regression coefficient of bx is positive. The result of R Squere is that Fadira Pekanbaru Bookstore is influenced by customer satisfaction of 52.6% while the remaining 47.4% is influenced by other variables not examined